2017
DOI: 10.1111/ecc.12798
|View full text |Cite
|
Sign up to set email alerts
|

Threatened fertility: A longitudinal study exploring experiences of fertility and having children after cancer treatment

Abstract: Infertility is a recognised potential sequel of cancer treatment which impacts negatively on the quality of survival. The aim of this study was to explore how men and women experience the threat of infertility by cancer treatment and individuals' thoughts about having children after cancer during the first 2 years following diagnosis. Nine women and seven men (aged 24-41) participated in two interviews in this longitudinal interview study, after the initiation of cancer treatment and 2 years thereafter. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Consistent with previous research among infertile, but otherwise healthy couples and adult‐onset cancer survivors, our findings highlight the emotional strain of infertility/unsuccessful pregnancy attempts. However, some childhood cancer survivors in this study also reported positive or no consequences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous research among infertile, but otherwise healthy couples and adult‐onset cancer survivors, our findings highlight the emotional strain of infertility/unsuccessful pregnancy attempts. However, some childhood cancer survivors in this study also reported positive or no consequences.…”
Section: Discussionsupporting
confidence: 90%
“…Research among infertile, but otherwise healthy individuals indicated that unsuccessful attempts to conceive/sterility can cause distress and strain romantic relationships due to frustration, conflicts, and/or break‐ups . Similar findings have been reported among survivors of adult‐onset cancer who wanted (additional) children after treatment, and the cancer experience may also alter whether survivors desire to have children . Although adult survivors of childhood cancer may experience comparable difficulties as they are frequently faced with fertility problems (eg, reduced sperm count/ovarian reserve) or infertility/sterility in adulthood, little research has focused on this unique and diverse population.…”
Section: Introductionmentioning
confidence: 85%
“…15 Many cancer survivors of reproductive ages want to have children and desire information about their fertile ability. 5,10,18,[22][23][24] For young women who are at risk for premature menopause, this information is crucial in order to make informed decisions about timing of parenthood and post-treatment oocyte cryopreservation.…”
Section: Timing Of Discussionmentioning
confidence: 99%
“…Also, among patients diagnosed as teenagers or young adults, communication about fertility issues should be repeated when the patient returns for follow up after completion of cancer treatment . Many cancer survivors of reproductive ages want to have children and desire information about their fertile ability . For young women who are at risk for premature menopause, this information is crucial in order to make informed decisions about timing of parenthood and post‐treatment oocyte cryopreservation.…”
Section: Physicians' Perspectives and Challengesmentioning
confidence: 99%
“…This pressure could be the reflection of a judgment-bias regarding the clinicians' perceptions when considering the importance patients gave to their fertility, after surviving cancer, which emphasizes the importance of how the information was delivered that could have impacted the patient's decision-making processes. Moreover, the need for more information seems to be less prominent at diagnosis, but increases during and after systemic anticancer treatments [42]. after treatment, patients seem to recognize the importance of discussing fertility before the beginning of the treatment and revealed some disappointment regarding the quality and quantity of the information received [42].…”
Section: Patient Information Needs Regarding Fertility Preservationmentioning
confidence: 99%